SharePoint 2013 user's guide : learning microsoft's business collaboration platform - Smith, Tony (Apress Imprint: Apress, 2013)
Microsoft SharePoint 2013 provides a collection of tools and services you can use to improve user and team productivity, make information sharing more effective, and facilitate business decision-making processes. In order to get the most out of SharePoint 2013, you need to understand how to best use the capabilities to support your information management, collaboration, and business process management needs. The SharePoint 2013 User's Guide is designed to provide you with the information you need to effectively use these tools. Whether you are using SharePoint as an intranet or business solution platform, you will learn how to use the resources (such as lists, libraries, and sites) and services (such as search, workflow, and social) that make up these environments. In the fourth edition of this bestselling book, author Tony Smith walks you through the components and capabilities that make up a SharePoint 2013 environment. He provides step-by-step instructions for using and managing these elements, as well as recommendations for how to best leverage them. The author has brought together this information based on his extensive experience working with these tools and with business users who effectively leverage these technologies within their organizations. These real-world experiences were incorporated into the writing of this book to make it easy for you to gain the knowledge you need to make the most of the product. Pick up a copy of the SharePoint 2013 User's Guide today.